2015
DOI: 10.1021/acscatal.5b02483
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Promoted Pd(II)-Catalyzed Functionalization of Unactivated C(sp3)–H Bond: Regio- and Stereoselective Synthesis of Arylated Rimantadine Derivatives

Abstract: Stereoselective functionalization of the adamantyl bridge methylene C­(sp3)–H bonds is a rather appealing, yet challenging strategy due to the bulky and unactivated nature. Here we present a palladium-catalyzed C­(sp3)–H arylation/hetereoarylation of the antivirus drug rimantadine with the picolinamide moiety as the bidentate directing group and a mono-N-protected amino acid (MPAA) as the ligand. Multisubstituted rimantadine substrates and diverse aryl/heteroaryl iodides are well tolerated, and a series of opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…It was reported that the reaction of 1-adamantanecarbonitrile with ethyl magnesium bromide and titanium tetraisopropoxide afforded 4 in 52% yield. 15 We tested twice this procedure with 1-adamantanecarbonitrile and methylmagnesium bromide yielding in our hands 3 with only 10% yield, which is lower than the ∼50% yield starting from 6 or 1-adamantanecarboxylic acid (Scheme 2). Table 1 includes thermodynamic parameters of binding against M2TM WT and M2TM S31N.…”
mentioning
confidence: 82%
“…It was reported that the reaction of 1-adamantanecarbonitrile with ethyl magnesium bromide and titanium tetraisopropoxide afforded 4 in 52% yield. 15 We tested twice this procedure with 1-adamantanecarbonitrile and methylmagnesium bromide yielding in our hands 3 with only 10% yield, which is lower than the ∼50% yield starting from 6 or 1-adamantanecarboxylic acid (Scheme 2). Table 1 includes thermodynamic parameters of binding against M2TM WT and M2TM S31N.…”
mentioning
confidence: 82%
“…The first diastereoselective functionalization of the 1-(1-aminoethyl)adamantane derivative 97 was presented with picolinamide (PA) as the directing group and a mono-N-protected amino acid (Boc-L-ILeu-OH) as the ligand (Scheme 41). 58 The diarylated compounds 98 were obtained in yields up to 91% with absolute diastereoselectivity. The precomplex C7 formed after the ligand exchange with Pd(OAc) 2 was isolated and characterized by 1 H and 13 C NMR spectroscopy.…”
Section: Scheme 38 β-Arylation Of a 1-(aminomethyl)adamantane Derivativementioning
confidence: 98%
“…The high efficiency and impressive functional group tolerance of Daugulis’ methodology to couple aryl halides with C(sp 3 )–H bonds using bidentate auxiliaries 109120 have attracted several groups seeking to extend the coupling partner scope of this chemistry. For instance, Corey and coworkers developed a C(sp 3 )–H acetoxylation protocol of α-amino acid derivatives ( 117 ) in the presence of a Pd(OAc) 2 catalyst, manganese(II) acetate, oxone, and acetic anhydride in nitromethane to give 118 with good diastereoselectivity (Scheme 25).…”
Section: C(sp3)–h Activation Directed By Strongly Coordinating Auxmentioning
confidence: 99%